Analisis Perbandingan Hierarchical dan Non-Hierarchical Clustering Pada Data Indikator Ketenagakerjaan di Jawa Barat Tahun 2020 - Umi Syafiyah; Dita Putri Puspitasari; Iqbal Asrafi; Brian Wicaksono; Finer Mayland Sirait (Seminar Nasional Official Statistics, 2022)
The Covid-19 pandemic has had a significant impact on various sectors in Indonesia, including West Java Province. One of the affected sectors is the employment sector. West Java Province is the province with the highest Open Unemployment Rate (TPT) in Indonesia, after Banten Province. This is due to the increase in the labor force but not attributable to an adequate employment opportunity. The purpose of this study is to group regencies/cities in West Java Province based on employment indicators. In addition, this study also aims to present a comparison between the hierarchical cluster method, namely single linkage, average linkage, and complete linkage, and the non-hierarchical cluster method, namely k-means cluster. The results of the analysis show that the complete linkage method of 2 clusters is the most suitable method in grouping regencies/cities in West Java Province based on employment indicators. There are two groups formed based on complete linkage, namely: cluster 1 which consists of 18 regencies/cities with characteristics of good labor development and cluster 2 which consists of 9 regencies/cities is a cluster with characteristics of labor development that has not been maximized.